Some aspects concerning modifications of the list of prohibited substances and methods in sport - Pokrywka, A.; Kwiatkowska, D.; Kaliszewski, P.; Grucza, R. (Biology of Sport, 2010)
In 1967 the International Olympic Committee (IOC) founded Medical Commission to organize and supervise fight against doping. At that time, the Commission published the first list of substances prohibited for use in sport to meet the need of anti-doping testing at the 1968 Olympic Games. The Prohibited List included stimulants, sympathomimetic amines, narcotics (narcotic analgesics), antidepressants and tranquilizers. For years the list was expanding and underwent modifications, mainly prior to successive Olympic Games. Starting from 1 January 2004, the World Anti-Doping Agency (WADA) has assumed the role of the main coordinator in fight against doping. WADA significantly modified the list of prohibited substances and methods (the Prohibited List). These modifications initiated changes, whose effects can be observed in three main areas of sport and anti-doping i.e. in: athletes, doping control laboratories, and sport entourage. In Poland, the removal some substances from the List or the addition other compounds to the basic List caused an increase of usage of pseudoephedrine and caffeine by athletes and a decrease of number of positive doping cases with cannabinoids and glucocorticosteroids. The annual modification of the Prohibited List by WADA and subsequent introduction of new examples of prohibited substances strengthened the world anti-doping system. Considering the open character of the list a regular update would be expected, especially indicating prohibited or permitted status of new substances and drugs. It would be advisable to publish, on the WADA website, some additional information regarding those substances which cause the most interpretation problems.